Benin : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of a Performance Criterion, and Request for Extension of the Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report, 2008)
Benin showed good macroeconomic performance under the Poverty Reduction and Growth Facility (PRGF) program. Executive Directors agreed that strong revenue performance helped to underpin improvement in public finances and economic growth while keeping inflation low. They stressed the need to adhere to prudent fiscal and monetary policies and also to build a sound banking system. They welcomed reforms to enhance the efficiency and competitiveness of the Port of Cotonou. They emphasized the need for the implementation of structural reforms, the improvement of the land tenure system, and the judiciary for growth and economic diversification.